The Legal Protection Against Debtors Whose Objects Of Guarantee Are Auctioned By The Bank Through Office Of State Wealth Services And Auction In Medan City - Jericho David Kelana Zendrato, Ralph Alfred (Cattleya Darmaya Fortuna, 2024)
This research takes the form of an analysis of the form of legal protection for debtors whose collateral objects are auctioned by banks through the State Property and Auction Services Office in Medan City (Decision Study: 993/Pdt.G/2022/PN.Mdn). The plaintiff in this case made a loan to Defendant I where the loan was taken away to Defendant II and reached Defendant III where Defendant III placed three collaterals where when there was a default on both parties the Defendant as the holder of the mortgage rights. was given by the plaintiff to conduct an auction at a below market price without any notification to the plaintiff in which case the plaintiff felt disadvantaged. This research was carried out using a descriptive approach with qualitative methods with a normative juridical type of research based on secondary data sources taken from case studies of court decisions and laws with analysis using related legal materials. The results of this research obtained results in the form of knowledge related to the form of analysis of judges' decisions regarding the legal protection of debtors whose collateral objects are auctioned by banks through the KPPN and Medan City Auction, showing that debtors have clear rights to obtain appropriate legal protection. Judges must ensure that banks fulfill their obligations to provide clear and complete information, transparent auction procedures, debtors' rights to participate in auctions, and legal protection for debtors. Thus, the debtor can obtain fair compensation if the debtor fails to pay the credit.